Removal of 2,4-Dichlorophenoxyacetic Acid Using Fe(OH)3 Based Complex Adsorbent - Hoai Nam, Nguyen; Van Bay, Dao; Ngoc Khue, Do; Van Chung, Tran (Asian Journal of Chemistry, 2013)
The adsorbents based on Fe(OH)3 containing SiO2 and Fe(0) powders (denoted 3TP) were prepared and used for removal of 2,4-dichlorophenoxyacetic acid from water. The characteristics of this adsorbents were determined and indicated that the presence of SiO2 and Fe(0) powders can enhance the amorphous structure of adsorbents, desired for the adsorption. The adsorption of 2,4-dichlorophenoxyacetic acid onto adsorbents was studied. The adsorption process occurs predominantly via chemisorptions of 2,4-dichlorophenoxyacetic acid onto adsorbents. The adsorption characteristics including kinetic thermodynamic parameters were examined. The experimental data shown that this is an endothermic, spontaneous adsorption process.